Association between Haptoglobin Phenotypes and Dyslipidemia as a Risk Factor of Cardiovascular Disease Among Ghanaian Hiv/Aids Patients - Tagoe, I.N.A. (University of Ghana, 2016)
Cardiovascular disease (CVD) is one of the major complications in patient with human immunodeficiency virus (HIV) infection. The development of dyslipidemia as primary risk factor of CVD has been attributed to the contribution of oxidative stress. Studies have reported that these complications can be averted in HIV/AIDS with an effective antioxidant system. The association between haptoglobin phenotypes and dyslipidemia as risk factor to the development of cardiovascular disease in Ghanaian HIV/AIDS patients was studied in this cross-sectional study. A total of 180 HIV/AIDS patients were recruited from the Fevers unit of the Korle-Bu Teaching Hospital, Ghana. Patients on HAART were 105 (58.7%), was made up of 46 (43.8%) males and 59 (56.2%) females. HAARTNaïve patients were 75 (41.6%) comprising of 19 (25.3%) males and 56 (74.6%) females. The control group (100) was made up of 39 (39 %) males and 61 (61%) females. In this study, biochemical parameters such as total cholesterol (TC), triglycerides (TG), LDL and HDL were measured. The HIV viral RNA and cluster of differentiation (CD4) count were also measured among HIV patients. Haptoglobin phenotype was determined on polyacrylamide gel electrophoresis. The mean diastolic blood pressure (DBP), body mass index (BMI), visceral fat and body fat of patients compared with apparently health controls were not statistically significant (p > 0.05). However, the mean systolic blood pressure was significantly elevated in patients on HAART compared to those naïve of antiretroviral treatment. Mean hemoglobin level in HAART-naïve patients was significantly low (p < 0.05) when compared to mean hemoglobin of HAART treated patients and control group. However, lactate dehydrogenase (LDH) activity was significantly raised in both HAART and HAART-naïve patients than the controls (p < 0.0001). The CD4 count in the patients on treatment was significantly elevated than the HAART-naïve group (p < 0.0001). The mean HIV viral RNA level in HAART-naïve patients compared to those on treatment was significantly higher (p < 0.01). Malondialdehyde (MDA) was significantly elevated in both HAART and HAART-naïve patients compared to control group. The study participants had varied but significant mean MDA in relation to stratified CD4 counts. Generally, lipid parameters were altered among the study population. Total cholesterol, triglycerides, LDL, TC/HDL, LDL/HDL ratios and atherogenic index of plasma (AIP) were elevated in HIV patients (p < 0.0001) with significant variations between HAART and HAART-naïve groups when compared to the control group. The mean HDL level was significantly low in HIV groups whiles it was increased in the control group. The odds for developing hypercholesterolemia was 3.54 times more in patients on HAART compared to HAART-naïve patients. Again, HDL was significantly lower in HAART patients compared to HAART-naïve patients (OR = 0.22, p < 0.001). The CD4 count was negatively correlated with AIP. Elevated MDA was shown to occur in subjects with Hp2-2 compared to the other phenotypes. Patients with HIV expressing Hp2-2 were 1.29 times at risk of developing CVD although not significant compared to the other phenotypes. Haptoglobin phenotype therefore may not be a risk factor for the development of CVD in Ghanaian HIV/AIDS patients.
Thesis(MPhil) - University of Ghana, 2016
Keywords: Association; Haptoglobin; Phenotypes; Dyslipidemia; Ghanaian; Hiv/Aids Patients; Risk Factor; Cardiovascular Disease